The impact of internet finance on green technology innovation in manufacturing companies --mediating role based on financing constraints - Yu, Yaguai; Li, Yuting; Ni, Taohan; Gao, Chuming (Frontiers in Environmental Science, 2023)
In order to empirically analyze the relationship between Internet finance and green technology innovation of manufacturing enterprises, this paper chooses listed manufacturing companies from 2011 to 2020 as its samples. It then builds a panel regression model, uses a causal stepwise regression test to look at the mediating effect of financing constraints in the role of Internet finance on green technology innovation. The findings demonstrate that the growth of Internet finance can significantly ease the financing challenges faced by industrial businesses and foster their use of green technologies. Further research revealed that firms located in less developed areas of central and western China, in regions with weaker environmental rules and smaller scale, played a greater role in fostering green technology innovation.As a result, enhancing the Internet finance incentive system for enterprise green technology innovation can effectively combine Internet finance development and enterprise green innovation, advance the development of ecological civilization, and serve as a crucial guide for decision-making in order to help China reach its "double carbon" goal.